The Dynamics of Religious Education in Higher Education - Faridi Faridi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to identify and understand the dynamics of religious education as indicated by students' attitudes from non-Muhammadiyah backgrounds to the dynamics of spiritual practice at the Faculty of Islamic Religion, University of Muhammadiyah Malang.. This research uses a qualitative approach with the type of case study. The data collection technique is done through observation, interviews, and documentation. At the same time, the data analysis is done through collection, condensation, presentation, followed by concluding. The study results show that religious practices that non-Muhammadiyah students often observe include; Qunut, the number of rakaah in Tarawih prayer, Tawassul, Dhikr together after fardhu prayer with a bright voice (jahr). Students consider the ordinance of worship as unimportant, and it is a subjective choice that must be respected and should not be disputed. On the one hand, non-Muhammadiyah students remain committed to sticking to the worship traditions that have been practiced since childhood. However, the practice of worship is still based on Fiqh, so it is flexible and dynamic.